OXIDATIVE STRESS INDUCED BY HUMIC ACID SOLVENT EXTRACTION FRACTION IN CULTURED RABBIT ARTICULAR CHONDROCYTES - Liang, H J; Tsai, C L; Lu, F J (Journal of Toxicology and Environmental Health, Part A, 1998)
Kashin-Beck disease (KBD) , an endemic, chronic osteoarthritic disorder with necrosis of chondrocytes, commonly occurs in China. The humic substance present in the drinking water of endemic areas has been proposed as one of the causative factors. In this study an in vitro cell culture system was used to investigate the damaging effects of humic acid (HA), a constituent of humic substance, on cultured rabbit articular chondrocytes. The commercial Aldrich humic acid (AHA) was fractionated with a series of organic solvents including n -hexane, benzene, ethyl acetate, and methanol. Among the several fractions of AHA, the ethyl acetate fraction (AHA-[EA]) displayed the most potent inhibitory effect on the survival of chondrocytes in clonogenic assays. Cellular injury induced by AHA-[EA] was evaluated by measuring cell viability with methylthiazol tetrazolium (MTT) and by determining the release of intracellular lactate dehydrogenase (LDH). Incubation of chondrocytes with AHA-[EA] (100-500 mug/ml) for 12 h produced a concentration-dependent decrease in cell viability and increase in LDH release. In addition, AHA-[EA] triggered lipid peroxidation manifested by elevated malondialdehyde (MDA) formation. In chemiluminescence assay, AHA-[EA] at the concentrations of 150-600 mug/ ml caused 6- to 15-fold increases of luminol-amplified chemiluminescence responses, which are considered to reflect the production of hydrogen peroxide (H2O2). Moreover, pretreating the cells with 500-750 U/ml of catalase significantly prevented the loss of cell viability, while superoxide dismutase (SOD) enhanced the adverse effect of 300 mug/ml AHA-[EA]. Data suggest that the injury to chondrocytes induced by AHA[EA] may be first through O2 production, which is then converted into H2O2, thus initiating lipid peroxidation and leading to chondronecrosis observed in KBD.